O estudo dos implícitos na construção de pontos de vista : estratégias para a participação social de estudantes de 9º ano do ensino fundamental - Matos, Jussara dos Santos (2018)
This research aims to promote the construction of points of view (POV) among students of the 9th year of elementary school, enrolled in the ESWF School, located in the city of Estância - Sergipe, when they position themselves on themes related to social events. Because it is considered a category that is at the center of dialogism (RABATEL, 2005), the POV shows a cross-perspective, so it can be elaborated on the basis of different linguistic resources, among which are the strategies of constructing implicit and the direction of argumentative operators, which are linked to communicative purposes. Understanding as a linguistic and enunciative concept, the POV allows the expression of a subject's subjectivity through articulated positions in texts, which requires attention to the discursive and lexical choices, for the sentence structure, for the use of linguistic- arguments for the composition of paragraphs as well as for the mechanisms for progression of ideas that contribute to coherence. The intention to collaborate with the practices of other teachers directed the choice for the elaboration of a Pedagogical Notebook in which the sequence of activities directed to the production of POV by students of basic education will be found. This research is exploratory, since it brings together the teaching productions, made based on the theoretical basis and the needs of the classroom, whose results were obtained by the students after the analysis of the productions made in class. The set of pedagogical actions provided the students with writing practices whose productions allowed to observe that students have an ability to establish relationships between texts and social contexts, as well as to understand and use the linguistic elements that collaborate with the organization of a discursive positioning. We conclude, then, that student participation in language practices associated with social problems can be a satisfactory textual production strategy to the development of well elaborated points of view. In addition, we note that the teacher needs to assume the role of collaborator in this process through the articulation of activities and mediator at the moment of the exchange of views points.